Table of Content - - (Journal of agricultural, environmental and veterinary sciences, 2023)
Table of Content:1. Effect of Romifidine injection on clinical indicators, biochemical and hematological parameters in camelsMrs. Rahaf Al-Lazkani , Prof. Azzam Al-Omari2. Evaluation of the prerequisite programs for the Hazard Analysis and Critical Control Points Systemin some food factories in the Asir region, Saudi ArabiaAdel Mohammed Abumalih3. Attitudes of Farmers Towards Improvement Methods of Field Irrigation Systems at Some Villages in Al-Bustan Region, El-Beheira Governorate in Arabian Republic of EgyptDr. Ahmed Mohamed Ali Ghozlan4. Studying the effect of summer and winter seasons on some physiological and biochemical characteristics of blood in one-humped camels in Nineveh GovernorateLecturer \ Mohammad Salem Ibrahem5. Soil monitoring and land cover/land use assessment on the Blue Nile River Watershed, Blue Nile State – Sudan/ using remote sensing and other techniquesCo-Prof. Abass Mohamed El-Hag Hamed ,Co-Prof. El-Mamoun Haroun Osman Ishag ,Dr. Yousif Suleiman Abdalla Gumaa , Co-Prof. Motasim Hyder Abdelwahab Wedatallah6. The effect of portable air-purifiers in improving indoor air quality in pediatric intensive care units at two tertiary hospitals in Riyadh, Saudi ArabiaWaleed S. Al-Ghamdi , Dr. Aiman El-Saed , Majid M. Al-Shamrani , Ali Al-Rabou , Dr. Abdullatif A. Neamatallah , Dr. Fahad Al-Mehmadi7. Study of Milk Yield and Some of Its Chemical Components and Its Relationship with Lambs Growth of Awassi SheepLecturer \ Muthanna Fathi Abdullah
Keywords: Journal of Agricultural, Environmental and Veterinary Sciences